IMPROVING DIGITAL MARKETING PROFICIENCY FOR MSMES VIA COMMUNITY ENGAGEMENT: A CASE STUDY OF ISLAMIC ENTREPRENEURSHIP BOARDING SCHOOL PURWAKARTA - Asih, Rayi Retno Dwi; Indriyarti, Eko Retno; Octaviani, Dian; Sari, Wahyuni Rusliyana (Jurnal Pengabdian dan Kewirausahaan, 2025)
This community engagement program was implemented to enhance the digital marketing skills of micro, small, and medium enterprises (MSMEs) managed by the Islamic Entrepreneurship Boarding School Purwakarta, Global Cahaya Nubuwwah Insani (GCNI). Considering the increasing role of social media as a cost-efficient and wide-reaching marketing channel, the program provided contextual training tailored to the needs of GCNI’s coffee shop business unit. The activities included comprehensive needs assessment, situational analysis, and interactive workshops focusing on social media optimization, digital branding, and practical content creation. Evaluation results indicated strong benefits, with 84.38% of participants rating the program as highly useful and 15.63% as moderately useful. A key contribution of this initiative was its ability to integrate digital marketing strategies with institutional identity and local cultural branding, thereby strengthening both business visibility and community relevance. Despite these achievements, challenges were observed in terms of varying levels of digital literacy among participants and the limited duration of the program, which restricted opportunities for long-term skill reinforcement. To improve future outcomes, blended learning approaches and collaborations with digital practitioners are recommended to provide sustained mentoring and broader impact. Overall, this program demonstrates how community engagement can effectively empower institutionally managed MSMEs by embedding digital marketing capabilities into their entrepreneurial ecosystem.